2016
DOI: 10.1111/cwe.12161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parental Migration on Mental Health of Left‐behind Children: Evidence from Northwestern China

Abstract: China's rapid development and urbanization have induced large numbers of ruralresidents to migrate from their homes in the countryside to urban areas in search of higher wages. It is estimated that there are more than 60 million "left-behind children" (LBC) remaining in the countryside after their parents migrate, typically living with surrogate caregivers. Extensive research has focused on the impact of parental outmigration on children's mental health, but less attention has been paid to the effects of paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 22 publications
2
51
1
1
Order By: Relevance
“…For instance, using data collected in Beijing in , Lin et al (2011 found that both the experience of discrimination and perceived social inequity were strongly associated with mental illness among rural migrants. Drawing on a panel dataset of more than 19,000 students from 252 rural primary schools in northwestern China, Shi et al (2016) reported a significant and negative association between parental out-migration and the mental health of left-behind children in rural China. Similarly, a different study by Lu et al (2012) also suggested that adults in rural households with out-migrants are at a higher risk of depression than those in households without out-migrants, despite the fact that monetary remittances can compensate for the mental cost of out-migration.…”
Section: Does Hukou Matter For Mental Health? Stratification and Mentmentioning
confidence: 99%
“…For instance, using data collected in Beijing in , Lin et al (2011 found that both the experience of discrimination and perceived social inequity were strongly associated with mental illness among rural migrants. Drawing on a panel dataset of more than 19,000 students from 252 rural primary schools in northwestern China, Shi et al (2016) reported a significant and negative association between parental out-migration and the mental health of left-behind children in rural China. Similarly, a different study by Lu et al (2012) also suggested that adults in rural households with out-migrants are at a higher risk of depression than those in households without out-migrants, despite the fact that monetary remittances can compensate for the mental cost of out-migration.…”
Section: Does Hukou Matter For Mental Health? Stratification and Mentmentioning
confidence: 99%
“…A number of studies investigate the empirical correlation between migration and mental health outcomes of children. These papers provide evidence that children left‐behind are more prone to depression, anxiety, and other emotional and mental health problems, in response to the migration of their parents (Graham & Jordan, ; Shi et al., ; Wang et al., ; Zhao et al., ; Zhou et al., ), with children of migrant mothers most affected (Hewage, Bohlin, Wijewardena, & Lindmark, ). Closely related, some studies indicate that children living in migrant families are significantly more likely to have behavioural problems compared with those from nonmigrant households (Vanore et al., ; Wickramage et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…; Shi et al. ). In our migrant sample, most children in Shanghai and Suzhou were living with both parents, regardless of whether we look at all migrants (from dataset 1, rows 1 and 2), all migrants from Anhui (from dataset 2, rows 3 and 4), or all migrants from the three core study areas in Anhui (from dataset 3, rows 5 and 6).…”
Section: Resultsmentioning
confidence: 97%
“…; Shi et al. ). A higher score (which ranges from 0 to 15) indicates higher earning anxiety and a possible need for professional help.…”
Section: Methodsmentioning
confidence: 97%